2020
DOI: 10.1126/sciadv.aax6208
|View full text |Cite
|
Sign up to set email alerts
|

Citrus polymethoxyflavones attenuate metabolic syndrome by regulating gut microbiome and amino acid metabolism

Abstract: Metabolic syndrome (MetS) is intricately linked to dysregulation of gut microbiota and host metabolomes. Here, we first find that a purified citrus polymethoxyflavone-rich extract (PMFE) potently ameliorates high-fat diet (HFD)–induced MetS, alleviates gut dysbiosis, and regulates branched-chain amino acid (BCAA) metabolism using 16S rDNA amplicon sequencing and metabolomic profiling. The metabolic protective effects of PMFE are gut microbiota dependent, as demonstrated by antibiotic treatment and fecal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
215
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(225 citation statements)
references
References 40 publications
8
215
0
2
Order By: Relevance
“…58 Furthermore, researchers had found that purified citrus polymethoxyflavone-rich extract potently ameliorates HFDinduced metabolic disorder in a gut microbiota-dependent manner. 59 Neo is one of the several flavanone glycosides that are unique to certain citrus species and are among the , and TNF-α tested by qRT-PCR in the colon. ** P < .01 vs HFD → HFD; * P < .05 vs HFD → HFD.…”
Section: Discussionmentioning
confidence: 99%
“…58 Furthermore, researchers had found that purified citrus polymethoxyflavone-rich extract potently ameliorates HFDinduced metabolic disorder in a gut microbiota-dependent manner. 59 Neo is one of the several flavanone glycosides that are unique to certain citrus species and are among the , and TNF-α tested by qRT-PCR in the colon. ** P < .01 vs HFD → HFD; * P < .05 vs HFD → HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Many metabolic pathways are involved in the progression of diabetes, such as branched‐chain amino acid metabolism and lysine metabolism. Studies from Wang and Floegel et al suggested that amino acid metabolism plays an important role in the pathogenesis of diabetes, 8,10 and that branched‐chain amino acids and their metabolite (3‐hydroxyisobutyrate) are closely related to insulin resistance, 44,45 which suggests that the regulation of amino acids may be a molecular target for the development of drugs for the prevention and treatment of diabetes, and that the regulation of amino acid levels has the potential to treat diabetes 46 . Furthermore, 2‐aminoadipic acid, generated by lysine degradation, was a risk factor for diabetes from a 12‐year follow‐up study, which might be a potential modulator of glucose homeostasis 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbiota is known to be involved partly in regulating the biosynthesis, transport, and metabolism of BCAAs [ 99 , 100 ]. Prevotella copri and Bacteroides vulgatus are known to be the main species that contribute to the increased circulating BCAA levels [ 101 , 102 ], while a potentially causal role of Bacteroides ovatus in mediating the biosynthesis of BCAAs in metabolic disorders has also been suggested recently [ 103 ].…”
Section: Role Of Gut Microbiota In Host Energy Metabolism and Immumentioning
confidence: 99%
“…Interestingly, instant caffeinated coffee has been shown to prevent HFD-induced obesity, partly by reducing Firmicutes/Bacteroidetes ratio and serum BCAA level, while increasing serum SCFA level in rat [ 228 ]. Moreover, purified citrus polymethoxyflavone-rich extract can attenuate HFD-induced obesity by reducing Firmicutes/Bacteroidetes ratio and downregulating mTOR signaling [ 103 ]. Two plant-derived polyphenols, carnosol and curcumin, have been shown to prevent the increase in glycolysis and spare respiratory capacity in response to LPS stimulation in human dendritic cells [ 18 ].…”
Section: Effect Of Polyphenols On the Composition Of Gut Microbiotmentioning
confidence: 99%